Guarding Against Fiscal Risks in Hong Kong SAR. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Hong Kong SAR's government faces the dual challenges of volatile revenue and medium term spending pressures arising from a rapidly aging population. Age-related spending pressures raise long-run sustainability concerns, while revenue volatility creates risks to service provision, possibly entailing sudden tax changes, or even requiring new borrowing. After describing the risks associated with aging, the paper uses value at risk techniques to measure the value of the unanticipated risks posed by volatile revenue. The paper also describes the self-insurance value of Hong Kong SAR's traditionally high fiscal savings (reserves), and the impact alternate policy choices could have on revenue volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet